Galaxy Zoo: A correlation between coherence of galaxy spin chirality and star formation efficiency - Jimenez, R; Slosar, A; Verde, L; Bamford, S; Lintott, C; Schawinski, K; Nichol, R; Andreescu, D; Land, K; Murray, P; Raddick, M; Szalay, A; et al. (2009)
We report on the finding of a correlation between galaxies' past star formation activity and the degree to which neighbouring galaxies rotation axes are aligned. This is obtained by cross-correlating star formation histories, derived with MOPED, and spin direction (chirality), as determined by the Galaxy Zoo project, for a sample of SDSS galaxies. Our findings suggest that spiral galaxies which formed the majority of their stars early (z > 2) tend to display coherent rotation over scales of ~10 Mpc/h. The correlation is weaker for galaxies with significant recent star formation. We find evidence for this alignment at more than the 5-sigma level, but no correlation with other galaxy stellar properties. This finding can be explained within the context of hierarchical tidal-torque theory if the SDSS galaxies harboring the majority of the old stellar population where formed in the past, in the same filament and at about the same time. Galaxies with significant recent star formation instead are in the field, thus influenced by the general tidal field that will align them in random directions or had a recent merger which would promote star formation, but deviate the spin direction.